A giant posterior mediastinal malignant peripheral nerve sheath tumor and benign neurofibroma in body surface: a case report - Yan Zhang; Hongfei Cai; Guangchao Lv; Yang Li (BMC Surgery, 2021)
Abstract Background Neurofibromatosis comprises neurofibromatosis type 1 (NF1) and type 2 (NF2). Major tumor type of NF1 are neurofibroma recognized as benign peripheral nerve tumor, malignant peripheral nerve sheath tumor (MPNST), and glioma. Case presentation We report a woman with a special condition, whose tumors in body surfaces were benign neurofibroma and tumors in posterior mediastinum are MPNST. The chest-enhanced CT suggested a round soft tissue density in posteriormediastium. The diagnosis was established by pathology and immunohistochemistry. A single-stage thoracoscopic mediastinal mass resection was performed. The whole operation went smoothly and the CT scan of lungs did not show relapse of tumor three months later. Conclusions The appearance of neurofibroma should draw particular attention to the possibility of developing MPNST. More careful imaging examinations should be carried out, and pathological examination could diagnose it.